Mössbauer spectroscopy investigation of magnetic nanoparticles incorporated into carbon nanotubes obtained by the injection CVD method - Prudnikava, A.L.; Fedotova, J.A.; Kasiuk, J.V.; Shulitski, B.G.; Labunov, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
This paper is devoted to the investigation of phase composition of the
magnetic filler located inside multi-wall carbon nanotubes (CNTs) using Mössbauer
spectroscopy, scanning electron microscopy (SEM) and transmission electron
microscopy (TEM). CNTs were obtained by the injection CVD method using ferrocenexylene
solution under various conditions (i.e., the ferrocene concentration cx (1%, 5%,
and 10%), slow or fast cooling down rates of the synthesis reactor, temperature in the
reaction zone during synthesis), which can influence the magnetic properties of CNTs
owing to different contribution of Fe-containing phases. SEM and TEM methods were
applied to investigate morphology and structure of the synthesized material. It was
shown that Fe₃C phase formation is favorable at high content of the catalyst in the
feeding solution (10%), relatively low temperatures (775 ºC) during CNTs synthesis, as
well as long duration of the CNTs growth process (5 min). The cooling rate of the reactor
after CNTs synthesis was not crucial to iron phase contribution in our experiments.